Anterior choroidal artery and fetal-type posterior communicating artery origin transposition: a case report - Lu, Zhiyong; Ma, Lin (Frontiers in Surgery, 2026)
The Anterior Choroidal Artery (AChA) is an important intracranial artery, mainly supplying blood to key structures such as the internal capsule, optic tract, and lateral geniculate body. Typically, the AChA originates from the internal carotid artery (ICA) as the most distal branch, between the site of origin of the posterior communicating artery (PCoA) and the terminal bifurcation of the ICA. But there are occasional anatomical variations. Understanding these anatomical variations is vital for neurosurgical or neurointerventional procedures, as accidental damage to the AChA can lead to serious consequences. This article described fusiform dilation of ICA and the origins of AChA and PCoA from ICA in exchanged positions.